Mortality and high risk of major adverse events in patients with COVID-19 and history of cardiovascular disease. Issue 1 (8th April 2021) - Tessitore, Elena; Carballo, David; Poncet, Antoine; Perrin, Nils; Follonier, Cedric; Assouline, Benjamin; Carballo, Sebastian; Girardin, François; Mach, Francois
Abstract : Objective: History of cardiovascular diseases (CVDs) may influence the prognosis of patients hospitalised for COVID-19. We investigated whether patients with previous CVD have increased risk of death and major adverse cardiovascular event (MACE) when hospitalised for COVID-19. Methods: We included 839 patients with COVID-19 hospitalised at the University Hospitals of Geneva. Demographic characteristics, medical history, laboratory values, ECG at admission and medications at admission were collected based on electronic medical records. The primary outcome was a composite of in-hospital mortality or MACE. Results: Median age was 67 years, 453 (54%) were males and 277 (33%) had history of CVD. In total, 152 (18%) died and 687 (82%) were discharged, including 72 (9%) who survived a MACE. Patients with previous CVD were more at risk of composite outcomes 141/277 (51%) compared with those without CVD 83/562 (15%) (OR=6.0 (95% CI 4.3 to 8.4), p<0.001). Multivariate analyses showed that history of CVD remained an independent risk factor of in-hospital death or MACE (OR=2.4; (95% CI 1.6 to 3.5)), as did age (OR for a 10-year increase=2.2 (95% CI 1.9 to 2.6)), male gender (OR=1.6 (95% CI 1.1 to 2.3)), chronic obstructive pulmonary disease (OR=2.1 (95% CI 1.0 to 4.2)) and lung infiltration associated with COVID-19 at CT scan (OR=1.9 (95% CI 1.2 to 3.0)). History of CVD (OR=2.9 (95% CI 1.7 to 5)), age (OR=2.5 (95% CI 2.0 to 3.2)), male gender (OR=1.6 (95% CI 0.98 to 2.6)) and elevated C reactive protein (CRP) levels on admission (OR for a 10 mg/L increase=1.1 (95% CI 1.1 to 1.2)) were independent risk factors for mortality. Conclusion: History of CVD is associated with higher in-hospital mortality and MACE in hospitalised patients with COVID-19. Other factors associated with higher in-hospital mortality are older age, male sex and elevated CRP on admission.